2002
DOI: 10.1046/j.1442-2042.2002.00519.x
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor effect of reduction of 150‐kDa oxygen‐regulated protein expression on human prostate cancer cells

Abstract: Background : The 150-kDa oxygen-regulated protein ORP150, a new member of the heat shock protein family that functions as a molecular chaperone in the endoplasmic reticulum, was found to increase in infiltrating cancer cells. Since enhancement of ORP150 expression and the presence of vascular endothelial growth factor (VEGF) in human prostate cancer glands were immunohistochemically demonstrated, we examined whether transduced antisense ORP150 cDNA can reduce angiogenicity and tumorigenicity through suppressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 15 publications
0
34
0
1
Order By: Relevance
“…(4) ORP150: forward primer 5′-ACACTCCGAGACCTGGAGAA-3′ and reverse primer 5′-CAACACAGGCTTCTCTGTGG-3′, 480 bp [23]; …”
Section: Methodsmentioning
confidence: 99%
“…(4) ORP150: forward primer 5′-ACACTCCGAGACCTGGAGAA-3′ and reverse primer 5′-CAACACAGGCTTCTCTGTGG-3′, 480 bp [23]; …”
Section: Methodsmentioning
confidence: 99%
“…29 Miyagi et al showed that tumorigenicity is reduced in prostate cancer by decreasing HYOU1 expression. 30 Namba et al reported that up-regulation of HYOU1 in cancer cells can inhibit apoptosis. 31 We may assume that HYOU1 correlates with chemotherapeutic resistance and that gold compounds could overcome drug resistance by decreasing expression levels of apoptotic suppressors.…”
Section: Indicated Thatmentioning
confidence: 99%
“…It was reported that overexpression of GRP78 makes cells resistant to apoptosis induced by anti-cancer drugs (topoisomerase inhibitors) and ER stressors (tunicamycin and Ca 2+ ionophores) [75,76]. Furthermore, recent papers have described the up-regulation of ORP150 in clinically isolated tumors and cancer cell lines [77,78]. Therefore, we examined the role of ER chaperones in anti-tunmor effect of NSAIDs by examining the effect of ER chaperones on NSAID-induced apoptosis.…”
Section: Resultsmentioning
confidence: 99%